2018
DOI: 10.1016/j.artd.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Femoral condylar necrosis: treatment with hyperbaric oxygen therapy

Abstract: BackgroundOsteonecrosis of the knee (ONK) is a form of aseptic necrosis resulting from ischemia to subchondral bone tissue. Typically, treatment is invasive. Hyperbaric oxygen therapy (HBOT) may provide a noninvasive alternative by improving oxygenation and reperfusion of ischemic areas. This study evaluates the efficacy of HBOT in a series of ONK patients.MethodsThis retrospective study evaluates 37 ONK patients (29 male, 8 female; mean age ± 1 standard deviation: 54 ± 14); 83.7% of patients presented with Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…On the other hand, local deoxyhemoglobin levels decreased after tissues exposure to the same HBOT therapy protocol, but without significant difference between normal and necrotic areas, explained by local vasoconstriction. Promising results in the use of HBOT therapy for femoral head necrosis have also been reported in several other studies that have highlighted the HBOT therapy effects based on clinical outcome (range of motion, stabilometry and pain (6) or by magnetic resonance imaging (15,22). However, to our knowledge, the use of hyperspectral imaging to assess the effects of HBOT therapy on femoral condylar necrosis is presented for the first time in this study.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, local deoxyhemoglobin levels decreased after tissues exposure to the same HBOT therapy protocol, but without significant difference between normal and necrotic areas, explained by local vasoconstriction. Promising results in the use of HBOT therapy for femoral head necrosis have also been reported in several other studies that have highlighted the HBOT therapy effects based on clinical outcome (range of motion, stabilometry and pain (6) or by magnetic resonance imaging (15,22). However, to our knowledge, the use of hyperspectral imaging to assess the effects of HBOT therapy on femoral condylar necrosis is presented for the first time in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Studies reported radiographic improvement in FHN Stage I according to the Steinberg classification. Additionally, they reported better pain control, compliance, and range of motion (ROM) in FHN at Ficat stages I–II [ 27 , 89 , 90 , 106 , 107 ]. Hyperbaric oxygen therapy also enhances osteoclast and osteoblast function for bone remodeling and repair.…”
Section: Discussionmentioning
confidence: 99%
“…In pathologies characterized by osteonecroses, such as FHN and osteonecrosis of the knee [ 87 , 89 , 90 ], osteoradionecrosis, mandibular osteomyelitis, and dental implants, HBOT has been successfully used [ 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBOT also promotes bone regeneration by improving osteosynthesis, neoangiogenesis, and vasculogenesis. It has been successfully used in many pathologies characterized by osteonecrosis, such as avascular necrosis of the femoral head (AVNFH) and osteonecrosis of the knee [ 7 , 8 , 9 ]. In particular, referring to the oral and maxillofacial districts, HBOT increased the bone regeneration rate in osteoradionecrosis, mandibular osteomyelitis, and dental implants [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%